Assessing the effect of mergers and acquisitions on banks price efficiency: evidence from banking sectors in Middle East & North Africa (MENA) region - Mohamad Sindi, Sameer; Amin Noordin, Bany Ariffin; Ab Razak, Nazrul Hisyam; Kamarudin, Fakarudin (Serials Publications, 2017)
This article provides an empirical assessment of the profit, revenue and cost efficiency of 39 acquirer banks post M&A from 2000 to 2012 in the MENA region. This study employs the Data Envelopment Analysis (DEA), following the intermediation approach, to measure the level of efficiencies (profit, revenue and cost) of acquirer banks in MENA region. The findings indicated that there is a change in the level of profit, cost and revenue efficiency of acquirer banks post M&A compared to pre-M&A period. However, the changing in the level of efficiencies are not significant statistically. Thus, this study concludes that the M&A have no significant effect on profit, revenue and cost efficiency of acquirer banks in the MENA region. The findings from this study are expected to contribute significantly to the existing knowledge on the efficiency of banks post-M&A activities in the MENA region, bank's management, policymakers in the banking industries.